Anisotropic chemical strain in cubic ceria due to oxygen-vacancy-induced elastic dipoles. Issue 22 (24th May 2018) - Das, Tridip; Nicholas, Jason D.; Sheldon, Brian W.; Qi, Yue
Abstract : Accurate characterization of chemical strain is required to study a broad range of chemical–mechanical coupling phenomena. Abstract : Accurate characterization of chemical strain is required to study a broad range of chemical–mechanical coupling phenomena. One of the most studied mechano-chemically active oxides, nonstoichiometric ceria (CeO2− δ ), has only been described by a scalar chemical strain assuming isotropic deformation. However, combined density functional theory (DFT) calculations and elastic dipole tensor theory reveal that both the short-range bond distortions surrounding an oxygen-vacancy and the long-range chemical strain are anisotropic in cubic CeO2− δ . The origin of this anisotropy is the charge disproportionation between the four cerium atoms around each oxygen-vacancy (two become Ce 3+ and two become Ce 4+ ) when a neutral oxygen-vacancy is formed. Around the oxygen-vacancy, six of the Ce 3+ –O bonds elongate, one of the Ce 3+ –O bond shorten, and all seven of the Ce 4+ –O bonds shorten. Further, the average and maximum chemical strain values obtained through tensor analysis successfully bound the various experimental data. Lastly, the anisotropic, oxygen-vacancy-elastic-dipole induced chemical strain is polarizable, which provides a physical model for the giant electrostriction recently discovered in doped and non-doped CeO2− δ . Together, this work highlights the need to consider anisotropic tensors when calculating the chemical strain induced by dilute point defects in all materials, regardless of their symmetry.